Comparison of The Thickness of Free Anterolateral Thigh Flap in Different Fascial Planes: Clinical Results of Subfascial and Superficial Fat Flap - Tuluy, Yavuz; Bali, Zülfükar Ulaş; Ünsal, Merve Özkaya; Parspancı, Aziz; Yoleri, Levent; Çiçek, Çağla; Filinte, Gaye Taylan (Archives of Plastic Surgery, 2023)
Background The anterolateral thigh (ALT) flap is a preferred option in the reconstruction of a wide variety of defects, enabling multiple tissue components and thicknesses.Methods This study was conducted to investigate the correlation of the thickness of the traditional subfascial ALT flap and superficial fat flap with age, gender, and body mass index (BMI). A total of 42 patients (28 males and 14 females) were included in the study.Results Mean age was 50.2 (range, 16–75) years and mean BMI was 24.68 ± 4.02 (range, 16.5–34.7) kg/m2. The subfascial flap thickness was significantly thinner in male patients (16.07 ± 2.77 mm) than in female patients (24.07 ± 3.93 mm; p < 0.05), whereas no significant difference was found between male (4.28 ± 1.15 mm) and female patients (4.85 ± 1.09 mm) regarding superficial fat flap thickness (p = 0.13). The thickness of both flaps had a positive correlation with BMI, and the strongest correlation was found for subfascial ALT thickness in female patients (r = 0.81). Age had no effect on both flap thickness measurements. The anterior thigh is thicker in women than in men, although it varies according to BMI. This shows that flap elevation is important in the superthin plane, especially if a thin flap is desired in female patients in defect reconstruction with the ALT flap. Thus, a single-stage reconstruction is achieved without the need for a defatting procedure after subfascial dissection or a second defatting procedure 3 to 6 months later.Conclusion The appropriate ALT flap plane should be selected considering the gender and BMI of the patient.
Keywords: anterolateral thigh flap; reconstruction; free flap; superficial fat flap